Equivalent Circuit Analysis of the Side-Coupled Cavity Structure - Tripathi, P.; Kumar, A.; Dwivedi, S.; Jain, P.K. (Institute of Electrical and Electronics Engineers Inc., 2020)
The resonating frequency associated with the side-coupled cavity (SCC) has been theoretically explored using an equivalent circuit approach. This study is focused to estimate the coefficient of magnetic coupling factor in the context of its structural parameters, which has so far been experimentally evaluated. This article also proposed an empirical formula to calculate the fundamental-mode frequency that includes the effect of the magnetic-coupling factor, which was not considered in the previously reported research. To support this research study, the SCC has been designed and simulated with the help of 'CST Studio Suite.' The results obtained from the proposed empirical formula were compared with the simulation result so that theoretical analysis could be verified. After comparing the results, it was found that the relative error is below 1%, indicating that there is a good agreement between the results obtained from the theoretical and simulation techniques. © 1973-2012 IEEE.
Keywords: High-power microwave (HPM); side-coupled cavity (SCC); slow-wave structure (SWS)